Green and Cost-Effective Spectrophotometric Analysis of Diclofenac Sodium Using Mixed Hydrotropy - Ketan Soni; Kavita Sharma (Pharmaceutical Fronts)
Diclofenac sodium is a widely used non-steroidal anti-inflammatory drug with potent analgesic, anti-inflammatory, and antipyretic properties. However, its limited aqueous solubility poses challenges in pharmaceutical formulations and analytical quantification. To address this issue, various solubility enhancement techniques have been explored to improve its bioavailability and facilitate precise spectrophotometric analysis. Hydrotropic solubilization has been widely studied as an effective technique to improve the aqueous solubility of poorly water-soluble drugs. This study aimed to investigate an eco-friendly and efficient approach to enhance the solubility of diclofenac sodium, focusing on a mixed hydrotropic approach, ensuring reliable and accurate spectrophotometric estimation without the need for organic solvents. In this work, sodium citrate and N,N-dimethylurea were explored as hydrotropic agents. The selection was based on their complementary solubilization mechanisms. Sodium citrate enhances solubility through ionic interactions, whereas N,N-dimethylurea disrupts the water structure and forms hydrogen bonds with the drug. The results showed a synergistic effect of the combined use of these agents with a solubility of 63 mg/mL, which was significantly higher than that of individual use. Besides, the Fourier transform infrared (FTIR) spectroscopy confirmed hydrogen bonding when diclofenac sodium was dissolved in the hydrotropic blend, and X-ray diffraction analysis demonstrated a decrease in the crystallinity of the drug, indicating a transition to a more soluble amorphous state. The solubility studies, molecular docking, and recovery experiments confirmed the high accuracy and precision of the proposed method with percentage recoveries near 100%. In conclusion, this green and cost-effective approach eliminates the need for toxic organic solvents, making it a sustainable and scalable solution for the analysis and formulation of poorly water-soluble drugs.